PACKAGING SUPPLIER SELECTION MODEL BASED ON THE ANALYTICAL HIERARCHY PROCESS (AHP) METHOD OF A PHARMACEUTICAL COMPANY - Ardiprawiro (Asosiasi Dosen Muda Indonesia, 2022)
Suppliers selected based on a simple evaluation tend not to pay attention to the selection according to a particular method or system so that sometimes the process takes a lot of time and what has been decided is not in accordance with what is expected by the company as a consumer who buys the company's needs. This study aims to prove that the use of the AHP method helps the decision-making process faster and in accordance with the needs of pharmaceutical companies. The data used is primary data collected from employees of pharmaceutical companies. Data were collected using survey and interview techniques. The research analysis tools used are Analytical Hierarchy Process and Expert Choice v.11. The results showed that the use of the AHP method was proven to help in the selection of drug packaging suppliers in pharmaceutical companies more quickly and according to the company's needs.